2019
DOI: 10.1002/pssb.201900436
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Metal‐Organic Chemical Vapor Deposition Regrown n‐GaN

Abstract: GaN devices for high‐frequency and high‐power applications often need n‐doped GaN layers on top of their structures. Such layers can be either grown in an epitaxial reactor or formed by implantation or annealing of Si‐containing layers (e.g., a SiO2 mask). These processes are typically performed at high temperatures, which generate the undesired effect of atom diffusion between the different epitaxial layers; consequently, the electrical performance of the final device will be hampered. Herein, an optimized ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…In non-alloyed ohmic contacts the main challenge remains as the choosing of appropriate mask, regrowth temperature, post-annealing treatment and achieve proper surface passivation without effecting the device performance. Today mostly studied non-alloyed ohmic contact is regrowth of n+-GaN by using Moleculer Beam Epitaxy (MBE) or Metalorganic Vapor Phase Epitaxy (MOCVD) [15]. There are various studies which solve the main challenges by introducing additional pre-post treatments which creates new instabilities or increase the cost immensely.…”
Section: Azo For Gan Based High Electron Mobility Transistor (Hemt) Application As Contactmentioning
confidence: 99%
“…In non-alloyed ohmic contacts the main challenge remains as the choosing of appropriate mask, regrowth temperature, post-annealing treatment and achieve proper surface passivation without effecting the device performance. Today mostly studied non-alloyed ohmic contact is regrowth of n+-GaN by using Moleculer Beam Epitaxy (MBE) or Metalorganic Vapor Phase Epitaxy (MOCVD) [15]. There are various studies which solve the main challenges by introducing additional pre-post treatments which creates new instabilities or increase the cost immensely.…”
Section: Azo For Gan Based High Electron Mobility Transistor (Hemt) Application As Contactmentioning
confidence: 99%
“…Ohmic contacts for GaN HEMTs are commonly fabricated using Ti-or Ta-based metal stacks or regrown contacts. Planar metal-based contacts typically exhibit an R c of 0.2-0.4 Ω•mm, while regrown contacts achieve an R c smaller than 0.1 Ω•mm using molecular-beam epitaxy [4] or metalorganic chemical vapor deposition (MOCVD) [5,6]. However, the process of regrown contacts involves considerable complexity and planar metal-based ohmic contacts are therefore still the industrial standard.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] It is clear that experimental routes of obtaining Y‐rich AlYN alloys are to be found in order to settle this dispute. Recently, Leone et al reported on the metalorganic chemical vapor deposition (MOCVD) growth of AlYN with varied Y concentrations grown on GaN and AlN surfaces, [ 23 ] enabling new perspective on the challenges of pseudobinary nitride alloys.…”
Section: Introductionmentioning
confidence: 99%